1997
DOI: 10.1063/1.120424
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different interfacial environments on the optical nonlinearity of nanometer-sized CdO organosol

Abstract: The third-order optical nonlinearity χ(3) of nanometer-sized CdO with different interfacial environments has been measured using the Z-scan technique. The real and imaginary parts of χ(3) at 800 nm have been determined to be: −1.55×10−16 m2/W and 0.91 cm/GW for CdO–CTAB (cetyltrimethyl ammonium bromide) organosol, and −6.97×10−16 m2/W and 8.64 cm/GW for CdO–DBS (dodecylbenzene sulfonate) organosol. Origins of the optical nonlinearity and the effects of the interfacial conditions have been discussed. The optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…2͑d͒, we obtain n 2,PbSe values of −6.5 10 −7 cm 2 / W. These are among the highest values reported for colloidal semiconductor quantum dots. 4,5,9,10 The correlation between the absorbance and the nonlinear refractive index spectrum and the observation of refractive index saturation suggest that state filling lies at the origin of the observed nonlinear effects. Combining the pulse duration, intensity at the focus, and repetition rate of the laser with the lifetime of a single exciton ͑0.66 s for 5.4 nm Q-PbSe, determined from the luminescence decay͒, the steady state fraction of nanocrystals containing a single exciton can be calculated.…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations
“…2͑d͒, we obtain n 2,PbSe values of −6.5 10 −7 cm 2 / W. These are among the highest values reported for colloidal semiconductor quantum dots. 4,5,9,10 The correlation between the absorbance and the nonlinear refractive index spectrum and the observation of refractive index saturation suggest that state filling lies at the origin of the observed nonlinear effects. Combining the pulse duration, intensity at the focus, and repetition rate of the laser with the lifetime of a single exciton ͑0.66 s for 5.4 nm Q-PbSe, determined from the luminescence decay͒, the steady state fraction of nanocrystals containing a single exciton can be calculated.…”
Section: Samplementioning
confidence: 99%
“…Applications of colloidal semiconductor nanocrystals ͑or quantum dots͒ have already been explored in optoelectronic or photovoltaic devices ͑photodetectors, 1 light emitting diodes, 2 and lasers 3 ͒. An additional field of applications may follow from recent studies indicating that quantum dots show strongly enhanced nonlinear optical properties, 4 and behave as saturable absorbers. 5,6 Materials with a large and fast nonlinear refractive index can be used in devices such as Mach-Zehnder interferometers, 7 and absorption saturation is a necessary element in passive modelocked lasers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Here we not only focus on the efficient generation of light but also on the manipulation of light, taking advantage of unique optical properties of semiconductor quantum dots. Recent studies have already demonstrated that quantum dots show an enhanced nonlinear refractive index [6] and behave as saturable absorbers [7,8]. These effects can be used for instance to achieve all-optical switching [9].…”
Section: Introductionmentioning
confidence: 99%